2020
DOI: 10.1123/ssj.2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Sport Advocacy: The Art of Persuasion and Its By-Products

Abstract: Despite an increase of advocacy by established nongovernmental sport organizations, little is known about how advocacy is enacted and with what effects. Building conceptually on frame alignment theory and empirically on interview data from 19 Swedish Regional Sport Federations, this article investigates how advocates politicize sport to gain “insider status” and analyses the by-products of such efforts. This research demonstrates that the architecture of advocacy claims perpetuates a separation between organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…transformative effects of CCs' interaction style), we follow the views of Sieber (1981) and Hood (1991) around the propensity for policy instruments and organising more generally to have effects beyond what was intended. This has been shown in several studies situated in a sport context (Fahl en, 2017;Fahl en et al, 2015;Fahl en & Stenling, 2019;Sam, 2011;Stenling & Sam, 2020a, 2020bThompson et al, 2021; for conceptual discussions, see also Sam, 2009;Nagel et al, 2015) and can be attributed to the trade-offs between values that are invariably made in policy and organising processes. As an illustration, Thompson et al (2021) showed that English NSF sport development officers' management of tensions between centrally mandated policy priorities and sport clubs' orientation reduced SDO club relationship building, thus undermining long-term NSF developmental trajectories and sustainability.…”
Section: Institutionally Shaped Slb Interaction Stylesmentioning
confidence: 87%
See 1 more Smart Citation
“…transformative effects of CCs' interaction style), we follow the views of Sieber (1981) and Hood (1991) around the propensity for policy instruments and organising more generally to have effects beyond what was intended. This has been shown in several studies situated in a sport context (Fahl en, 2017;Fahl en et al, 2015;Fahl en & Stenling, 2019;Sam, 2011;Stenling & Sam, 2020a, 2020bThompson et al, 2021; for conceptual discussions, see also Sam, 2009;Nagel et al, 2015) and can be attributed to the trade-offs between values that are invariably made in policy and organising processes. As an illustration, Thompson et al (2021) showed that English NSF sport development officers' management of tensions between centrally mandated policy priorities and sport clubs' orientation reduced SDO club relationship building, thus undermining long-term NSF developmental trajectories and sustainability.…”
Section: Institutionally Shaped Slb Interaction Stylesmentioning
confidence: 87%
“…In addition to analysing CCs' institutionally shaped interaction style vis-a-vis clubs, another aim with this paper was to build on ideas (Sieber, 1981;Hood, 1991) and sport-specific empirical research (Fahl en, 2017;Fahl en et al, 2015;Fahl en & Stenling, 2019;Sam, 2011;Stenling & Sam, 2020a, 2020bThompson et al, 2021) around unintended effects of policy and organising processes to draw attention to the systemlevel transformative effects that may follow from what appears to be a rather microlevel practice. In this final part of the paper, we outline our second contribution by providing some illustrations of such possible effects of Swedish CCs' interaction style.…”
Section: Potential System-level Transformative Effectsmentioning
confidence: 99%
“…This paper emerged from a project that explores the emergence and various aspects of advocacy conducted by Swedish sport's 19 RSFs, and from which three papers have been published previously (Stenling and Sam 2019a, 2020. These three papers focused on why RSFs are taking a more active advocacy approach (Stenling and Sam 2019a), who conducts advocacy (Stenling and Sam 2019b), and the building blocks and architecture of externally directed messages (Stenling and Sam 2020). The focus of this paper is indeed salient, considering that Swedish sport -at all levelsconsists of voluntary associations, and that high emphasis is placed on its democratic selfgovernance system.…”
Section: Research Contextmentioning
confidence: 99%
“…However, for contextualisation, it is notable that RSFs carry out a wide range of advocacy activities (i.e., meeting with elected officials and administrators of public bureaucracies, submitting news-paper opinion pieces, participating in radio-shows, releasing self-produced film-clips, etc.) during which they translate internally shaped advocacy content into strategically fitted messages that aim to convince policy-makers and their administrators to make decisions that benefit Swedish sport and RSFs' own standing as political actors (Stenling and Sam 2019a, 2020.…”
Section: Sport Advocacy In Swedenmentioning
confidence: 99%
See 1 more Smart Citation